FCI: an R-based algorithm for evaluating uncertainty of absolute real-time PCR quantification - Verderio, Paolo; Pizzamiglio, Sara; Gallo, Fabio; Ramsden, Simon C (BMC bioinformatics, 2008)
Background FCI is an R code for analyzing data from real-time PCR experiments. This algorithm estimates standard curve features as well as nucleic acid concentrations and confidence intervals according to Fieller's theorem. Results In order to describe the features of FCI four situations were selected from real data collected during an international external quality assessment program for quantitative assays based on real-time PCR. The code generates a diagnostic figure suitable for assessing the quality of the quantification process. Conclusion We have provided a freeware programme using this algorithm specifically designed to increase the information content of the real-time PCR assay.